If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5k + -2 = 33 Reorder the terms: -2 + 5k = 33 Solving -2 + 5k = 33 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 5k = 33 + 2 Combine like terms: -2 + 2 = 0 0 + 5k = 33 + 2 5k = 33 + 2 Combine like terms: 33 + 2 = 35 5k = 35 Divide each side by '5'. k = 7 Simplifying k = 7
| 3(x+6)=6(2+y) | | 3x+8=-4x-6 | | 4(n+9)-3(2+n)= | | 5(6+n)-2(n-2)= | | 6r+2(r+4)= | | 2+3xy-4xy+6= | | (2x+6)(5x-13)=0 | | x-1.6x-2.6=0.6x+2.2 | | 2(2-x)-4(2x-1)=4(x-1)-3(2x-3) | | 0.33333+x=-0.53333 | | 4.8x+2=3.8x | | 4.8-2=3.8x | | 0.6w+-1w= | | 0.7-(x-2.5)=10.5 | | 13-(-4-x)=1 | | 5.3+9.2x=7.4-8.8 | | 2x+x-12=0 | | 2.3x+6.8=3.94x-3.44 | | 4*(2+x)-2*(x+3)= | | 4d+4=3d+9 | | -(2x-5)=4(x+2) | | 2+3x-(2x+3)= | | 8x+7=2x+10 | | 3x+2(x+10)+3= | | 2*(x+10)= | | (x^4+5x-3)(5x^4-x+2)= | | (x^4+5x-3)-(5x^4-x+2)= | | 3x-7=2x-(3-x+4) | | 4x+34=x/61 | | 4c-3a+5= | | (-x-1)-(x-2)= | | 5x-1=2x+23 |